Between ideology and experience; Siauw Giok Tjhan's legacy to his daughter Siauw May Lie - Liem, Maya H.T.; Taga-Tan, Ing Lwan (UI Scholars Hub, 2017)
The principal objective of this article is to focus on the life-story of Siauw May Lie and her views about her past. She is the daughter of the well-known, influential politician, Siauw Giok Tjhan. Between 1945 and 1965 Siauw Giok Tjhan was member of the Parliament of the Indonesian Republic and chairman of Baperki (Badan Permusyawaratan Kewarganegaraan Indonesia, 1954-1965). Her life-story fits into the category of respondents with a cumulative migration history. As the Chinese Indonesian Heritage Center (CIHC) of the KITLV believes that the recording of life-stories is a valuable addition to the collection of material heritage, the interview with Siauw May Lie about her life and opinions is an example of the interviews and part of the research conducted by the Oral History Project of the CHIC.